LncRNA MNX1-AS1 sustains inactivation of Hippo pathway through a positive feedback loop with USP16/IGF2BP3 axis in gallbladder cancer. (28th October 2022) - Liu, Shilei; Li, Huaifeng; Zhu, Yidi; Ma, Xiaoming; Shao, Ziyu; Yang, Ziyi; Cai, Chen; Wu, Ziyou; Li, Maolan; Gong, Wei; Wu, Xiangsong
Abstract: The long non-coding RNAs (lncRNAs) have been implicated in multiple human cancers, which may offer great potential as putative targets for cancer diagnosis and treatment. However, the roles of most lncRNAs in gallbladder cancer (GBC) remain poorly understood. The objective of this research involves investigating the clinical implications and underlying mechanism of lncRNA motor neuron and pancreas homeobo×1 antisense RNA 1 (MNX1-AS1) in GBC. This study shows that MNX1-AS1 expression is elevated in the tissues of GBC patients, and is strongly associated with reduced patient survival. Functionally, MNX1-AS1 significantly stimulates the proliferation and metastasis of GBC cells in vitro and in vivo. Mechanistically, MNX1-AS1 is transcriptionally activated by TEA domain family member 4 (TEAD4), and suppresses insulin-like growing factor 2 mRNA-binding protein 3 (IGF2BP3) degradation by recruiting ubiquitin specific peptidase 16 (USP16). Furthermore, MNX1-AS1/IGF2BP3 axis inhibits the Hippo signaling pathway and subsequently activates TEAD4, thereby forming a positive feedback loop. According to our results, MNX1-AS1 facilitates tumorigenesis, progression and metastasis of GBC through a MNX1-AS1/IGF2BP3/Hippo pathway positive feedback loop, which could be both diagnostically and therapeutically helpful in GBC. Highlights: MNX1-AS1 expression is upregulated in GBC and predicts poor prognosis. Overexpression of MNX1-AS1 facilitates the proliferation and metastasis of GBC cells in vitro and in vivo. MNX1-AS1 acts as a scaffold for recruiting USP16 to stabilize IGF2BP3. MNX1-AS1/IGF2BP3/Hippo pathway positive feedback loop contributes to GBC progression.